Implementasi Metode Simple Additive Weighting (SAW) Seleksi Pemberian Beasiswa - Karnadi, Very (LPPM STIKOM Tunas Bangsa, 2023)
Higher education is a dream for parents for their children. However, sometimes due to economic conditions parents are unable to pay for their children's education up to college level. Most children who live in remote areas have the desire to complete their studies, coupled with their achievement skills. Currently, there are many scholarships provided by each region to assist education for underprivileged children with predetermined criteria, including: they must have criteria for academic achievement, parent's job, parent's dependents, income and certificate of incapacity. The aim of this research is to make it easier for related parties to select residents who are entitled to receive assistance in continuing their studies. The method used is the SAW method. The way this method works is to take the Max value to produce a decision. Based on the final results of the ranking, GD received the 1st recommendation with a value of 0.8927, MB the 2nd recommendation with a value of 0.8427, CM the 3rd recommendation with a value of 0.7928, JP the 4th recommendation with a value of 0.7738, SL the recommendation 5th with a value of 0.7738 and lastly WP with a value of 0.426. Thus it can be concluded that the SAW method is able to solve the problem of providing scholarships to underprivileged students.